2016
DOI: 10.1038/srep25092
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a novel glucose metabolism in cancer: The role of endoplasmic reticulum beyond glycolysis and pentose phosphate shunt

Abstract: Cancer metabolism is characterized by an accelerated glycolytic rate facing reduced activity of oxidative phosphorylation. This “Warburg effect” represents a standard to diagnose and monitor tumor aggressiveness with 18F-fluorodeoxyglucose whose uptake is currently regarded as an accurate index of total glucose consumption. Studying cancer metabolic response to respiratory chain inhibition by metformin, we repeatedly observed a reduction of tracer uptake facing a marked increase in glucose consumption. This pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
87
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 51 publications
17
87
1
3
Order By: Relevance
“…A novel glucose metabolism involving a hexose-6-phosphate dehydrogenase located within the endoplasmic reticulum has recently been identified in multiple cancer cell lines. 55 Since GLUT8 is localized to the endoplasmic reticulum, it may play a role in this process through active hexose transport. The impact of GPR55 inhibition —with ( R,R’ )-MNF or other molecules— in this process and on overall metabolic reprogramming through decreased GLUT8 protein expression will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…A novel glucose metabolism involving a hexose-6-phosphate dehydrogenase located within the endoplasmic reticulum has recently been identified in multiple cancer cell lines. 55 Since GLUT8 is localized to the endoplasmic reticulum, it may play a role in this process through active hexose transport. The impact of GPR55 inhibition —with ( R,R’ )-MNF or other molecules— in this process and on overall metabolic reprogramming through decreased GLUT8 protein expression will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Marini et al (49) have estimated NAD + /NADH ratio in 4T1 cell lysates to be~1.7 as compared with NADP + /NADPH ratio of 0.5 using spectrophotometric assay. Wu et al (50) also reported NADPH level in 4T1 lysates to 120 pmol/100 mg proteins as compared with~120 NADP + level.…”
Section: Two-photon Fluorescence Lifetime Imaging Microscopymentioning
confidence: 99%
“…В недавних исследованиях пока-зано, что метформин реализует свой противоопухолевый эффект через гликолиз и пентозо-фосфатный путь, сни-жая уровень НАДФН [39]. Скорее всего окажется, что мет-формин реализует свое противоопухолевое действие че-рез эффект Варбурга / Кребтри.…”
Section: влияние метформина на энергетический обменunclassified